Nilai-nilai Orientasi Hasil dalam Peningkatan Kinerja Perawat dalam Pencegahan dan Pengendalian Infeksi di RS OMNI Alam Sutera - Nusrat, Mavika Tarika; Anindita, Rina; Kusumapradja, Rokiah (Lembaga Penerbitan Universitas Esa Unggul, 2020)
Leadership Style contributes greatly to the performance of nurses, as well as the organization's organizational culture in shaping values that will affect the performance of nurses in preventing and controlling infections related to hospital services. The purpose of this study was to determine the effect of leadership style, organizational culture and nurse performance on infection prevention and control in the Alam Sutera OMNI Hospital. The research uses quantitative research methods. The data source used is primary data, with data collection techniques in the form of questionnaires. The sample in this study amounted to 140 respondents. Data analysis method uses Structural Equation Modeling (SEM). From the results of testing the model has met the criteria of Goodness of fit. The results of the study show leadership style, organizational culture significantly influence nurse performance in infection prevention and control. The directional coefficient of leadership style on nurse performance in infection prevention and control is greater than the indirect coefficient indicating there is an indirect influence of leadership style on nurse performance in prevention and control of infection through organizational culture.Keywords: Leadership Style, Organizational Culture, Nurse Performance in infection prevention and control